Nilai-Nilai Pendidikan Dalam Ibadah Puasa - Ariqa Nur Salsabila; Dwi Syaputri; Sukma Hardana (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research discusses the educational values of fasting during Ramadan in Islam, with a focus on Surah Al-Baqarah verses 183-187. Fasting is not only a form of worship, but also a means of teaching patience, honesty, compassion and self-discipline. Surah Al-Baqarah verses 183-187 emphasizes the obligation to fast for Muslims to achieve devotion to Allah SWT. Fasting is a means of achieving piety and avoiding sin, as well as practicing self-discipline by performing worship according to God's guidance. The research method used is literature study by collecting data from various sources to support propositions and ideas. Fasting has health benefits, increases concentration, teaches sincerity, and trains patience. In addition, Ramadan fasting is mandatory for Muslims and is an effective medium for instilling and applying Islamic educational values, such as hard work, discipline, gratitude, learning and empathy towards others..